EFFECTIVENESS IMPROVEMENT OF INFORMATION SUPPORT IN UNIVERSITIES OF PHYSICAL EDUCATION - Svistelnik, Iryna (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article analyzes effectiveness of information support in universities of physical education at the present stage.